1992
DOI: 10.1002/ijc.2910520111
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in a low‐risk population. The influence of age and menstrual status on disease pattern and survival in Saudi Arabia

Abstract: Data on 130 women with invasive breast cancer, seen at our institution between April 1981 and November 1990, were retrospectively reviewed to assess the influence of age and menstrual status on the pattern and prognosis of their disease. Patients were mostly young (median age 40 years) and in 21 patients (16%) the diagnosis was established at the age of 30 years or younger. Eighty-six patients (66%) were under 50 and 82 patients (63%) were pre-menopausal. Pre-menopausal patients were more numerous than expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…54 There are few studies on cancer of the breast in Saudi Arab females. [23][24][25][26][27] In one study from a university teaching hospital in the Eastern Province, 25 130 females with breast cancer were studied, 80 of whom were Saudi Arabs. Their mean age was 43.4 years, which is close to our figure of 47.1 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 There are few studies on cancer of the breast in Saudi Arab females. [23][24][25][26][27] In one study from a university teaching hospital in the Eastern Province, 25 130 females with breast cancer were studied, 80 of whom were Saudi Arabs. Their mean age was 43.4 years, which is close to our figure of 47.1 years.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Few studies address themselves to the whole spectrum of breast diseases in Arab females in general. [20][21][22] Surprisingly, the subject of breast diseases in Saudi Arab females, except for a few studies, mostly on carcinoma of the breast, [22][23][24][25][26][27] has not been given its fair share of attention in the Saudi medical literature. We present here our findings in a retrospective survey of pathological material examined in our laboratory, spanning more than 26 years and giving insight into the changing pattern of breast diseases among Saudi Arab females during a period that has witnessed dramatic improvements in social and economic conditions in Saudi Arabia.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] For example, papers from Tunisia report observations of rapidly progressing breast cancer in young women, suggestive of an inflammatory breast cancer histology. [5][6][7][8] In addition, others have reported that the majority (>50%) of breast cancer cases are diagnosed among women less than 50 [1,3,9] years of age; this is in comparison to US statistics which show that 22% of breast cancer cases are diagnosed in women under 50.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the median age at diagnosis increased from 48 years in 1946-1959 to 53.9 years in 2000-2001. Similarly, in China, the median age at diagnosis increased from 47.5 years in 1990 to 50 years in 2007 [8], and the median age at diagnosis in Saudi Arabia increased from 40 years in 1981-1990 [17] to 45 years in 2002 [15]. …”
Section: Cancer Prevalence and Epidemiology In Asiamentioning
confidence: 99%